Papel do sistema peptidérgico da nociceptina/orfanina FQ no comportamento depressivo em camundongos - Holanda, Victor Anastácio Duarte (2018)
Introduction: Nociceptin/orphanin FQ (N/OFQ) is the endogenous ligand of a receptor coupled to Gi protein named NOP receptor. Both N/OFQ and NOP receptor are widely expressed in brain areas involved in emotional processing. Clinical and preclinical evidence suggests antidepressant effects due to the blockade of the NOP receptor. This study aimed to investigate the role of the N/OFQ-NOP receptor system in the modulation of depressive-like behaviors in mice. Methods: Male Swiss and CD-1 mice and mice knockout for the NOP receptor (NOP (-/-)) were used in this study. The forced swimming test (FST) and the learned helplessness model (LH) were used to evaluate the depressive-like behavior of mice. Firstly, the effects of NOP agonists, antagonists and NOP(-/-) phenotype were investigated in the acquisition of the helpless behavior. The effects of co-administration of NOP agonists and classical antidepressant drugs on FST and LH were also investigated. Results: The NOP agonists, Ro 65-6570 (0.01-1 mg/kg, ip) and MCOPPB (0.1-10 mg/kg, ip), pre-induction sessions, increased percentage of mice developing the helpless phenotype. In contrast, blockade of NOP receptor with the antagonist SB-612111 (1-10 mg/kg, ip) reduced the percentage of mice exhibiting helpless behavior, and similar results were observed in NOP(-/-) mice. Interesting enough, under the same experimental condition, administration of nortriptyline (20 mg/kg, ip) did not alter the acquisition of helpless behavior. In the second part of this study, fluoxetine, nortriptyline, R-ketamine and SB-612111 induced similar antidepressant-like effects in the FST. Acute administration of NOP agonists, N/OFQ and Ro 65- 6570, did not induce any behavioral change. However, co-administration of N/OFQ and Ro 65-6570 blocked the antidepressant effects of SB-612111, fluoxetine and nortriptyline, but not R-ketamine, in FST. Likewise, the systemic injection of SB-612111, nortriptyline, but not R-ketamine, reversed the helpless behavior of mice. Co-administration of Ro 65-6570 blocked the antidepressant effects of SB-612111 and nortriptyline, but not R-ketamine. Conclusion: The activation of NOP receptor signaling facilitates, while its blockade, prevents the acquisition of helpless behavior. Furthermore, NOP receptor activation interferes with the antidepressant effects of monoaminergic drugs, including nortriptyline and fluoxetine, but not R-ketamine. Ultimately, these findings indicate a prodepressive profile due to the activation of the NOP receptor signaling during a stressful event, as well as contribute to the investigation about the role played by the N/OFQ-NOP receptor in the regulation of mood states.